1998
DOI: 10.1074/jbc.273.3.1825
|View full text |Cite
|
Sign up to set email alerts
|

Bait Region Involvement in the Dimer-Dimer Interface of Human α2-Macroglobulin and in Mediating Gross Conformational Change

Abstract: We have characterized four human ␣ 2 -macroglobulin (␣ 2 M) bait region variants (G679C, M690C, V700C, and T705C) to test the hypothesis that the bait regions are involved in the interface between noncovalently associated dimers. All four variants folded correctly as judged by many normal properties. However, the presence of a cysteine resulted in disulfide formation between otherwise noncovalently associated dimers in all four variants. The extent of disulfide cross-linking varied with the location of the cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The second-order rate constant calculated for the reaction of methylamine with the thiol ester was 11.5 M Ϫ1 s Ϫ1 . This compares with a value of 12.5 M Ϫ1 s Ϫ1 determined here for the thiol ester in human ␣ 2 M reacted with methylamine, which is closely similar to values determined elsewhere under similar conditions (35)(36)(37). Thus ECAM appears to contain an intact thiol ester that is protected from nucleophilic attack, even though the YY motif present in other ␣-macroglobulins does not seem to be present.…”
Section: Resultssupporting
confidence: 68%
“…The second-order rate constant calculated for the reaction of methylamine with the thiol ester was 11.5 M Ϫ1 s Ϫ1 . This compares with a value of 12.5 M Ϫ1 s Ϫ1 determined here for the thiol ester in human ␣ 2 M reacted with methylamine, which is closely similar to values determined elsewhere under similar conditions (35)(36)(37). Thus ECAM appears to contain an intact thiol ester that is protected from nucleophilic attack, even though the YY motif present in other ␣-macroglobulins does not seem to be present.…”
Section: Resultssupporting
confidence: 68%
“…Since new inter and intramolecular disulfide bonds were formed in a variant that contained a single cysteine residue within the bait region, it was proposed that the four bait domains are located in close proximity in the center of the molecule (36). However, the location of the new disulfide bonds in the amino acid sequence was not determined so that it is equally possible that they involve residues outside the bait regions and consequently their location and putative proximity remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that oxidation of 14 methionine residues and a single tryptophan residue results in the dissociation of tetrameric α 2 M into dimers (25). The exact positions of these residues have yet to be identified; however, we predict the central part of each α 2 M subunit containing the bait region (i.e., the target for proteolytic cleavage located between amino acid residues 666 and 706 in human α 2 M) to be important given that point mutations within the bait region have been shown to disrupt the noncovalent binding of α 2 M dimers (63). The bait region of human α 2 M is rich in methionine residues (i.e., M666, M673, M688, M697, and M713 located on each human α 2 M monomer; the latter is located just beyond the bait region), and in the intact tetramer, these methionine residues are closely aligned at the interface between the noncovalently associated α 2 M dimers (64).…”
Section: Discussionmentioning
confidence: 99%